2012
DOI: 10.2147/jbm.s25620
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of pernicious anemia

Abstract: Pernicious anemia (also known as Biermer’s disease) is an autoimmune atrophic gastritis, predominantly of the fundus, and is responsible for a deficiency in vitamin B12 (cobalamin) due to its malabsorption. Its prevalence is 0.1% in the general population and 1.9% in subjects over the age of 60 years. Pernicious anemia represents 20%–50% of the causes of vitamin B12 deficiency in adults. Given its polymorphism and broad spectrum of clinical manifestations, pernicious anemia is a great pretender. Its diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 33 publications
1
82
0
1
Order By: Relevance
“…Infantile onset symptoms usually result from infants of vegan mothers, infants of the mother with pernicious anaemia, congenital pernicious anaemia or a variant of juvenile pernicious anaemia 2 3. Prevalence of pernicious anaemia in the general population is 0.1% and it accounts as an aetiology for vitamin B 12 deficiency in up to 50% of adults 4. Pernicious anaemia is extremely rare in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infantile onset symptoms usually result from infants of vegan mothers, infants of the mother with pernicious anaemia, congenital pernicious anaemia or a variant of juvenile pernicious anaemia 2 3. Prevalence of pernicious anaemia in the general population is 0.1% and it accounts as an aetiology for vitamin B 12 deficiency in up to 50% of adults 4. Pernicious anaemia is extremely rare in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic factor antibodies were detected, but antibodies against parietal cell mass tested were negative in our case. Anti-intrinsic factor antibodies have 100% specificity and a low sensitivity of 35–50% while antiparietal cell antibodies have 50–80% sensitivity and a specificity of 90–98% 4 12 13. Although hypothyroidism was detected, we did not find any associated thyroid antibodies or an underlying Addison disease, coeliac disease, Sjögren syndrome, vitiligo or type I diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…To date, treatment of cobalamin deficiency related to Biermer's disease is based on parenteral vitamin B12, administered intramuscularly, under the form of cyanocobalamin, hydroxocobalamin, or methylcobalamin [3]. In France, only intramuscular cyanocobalamin is used for this indication (authorization of the French regulatory agency of drug use).…”
Section: Editorialmentioning
confidence: 99%
“…Pernicious anemia (PA) is currently considered as the main responsible factor for B12 malabsorption and deficiency (20%-50% of B12 deficiency cases in adults) [22]. Referring to Northern Europe, where the disease has been well documented, the estimated prevalence of PA is ~2% in subjects ≥ 60 years and nearly 0.1% in the general population [23].…”
Section: Searching For Recommendationsmentioning
confidence: 99%
“…However, most meta-analyses of randomised controlled trials show that there is no evidence to support the use of B12 supplements for prevention of cardiocerebrovascular diseases [21,26,27]. Recent statistics have revealed that the primary etiology of B12 deficiency in the elderly is foodcobalamin malabsorption (syndrome of non-dissociation of B12 from carrier proteins associated to hypochlorhydria) [23]. In the overall population, the main causes of mild to severe malabsorption have been ascribed to various gastrointestinal diseases and to consumption/abuse of drugs, such as nitrous oxide, gastric acid inhibitors or metformin [21].…”
Section: Searching For Recommendationsmentioning
confidence: 99%